2007
DOI: 10.1002/mus.20780
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative muscle measurements reveal a relationship between contracture formation and muscle remodeling

Abstract: Children with cerebral palsy often have spasticity of both the extensors and flexors, but how and why a flexion contracture of the wrist will develop during growth is not thoroughly understood. In order to understand the muscle adaptations that occur during contracture formation, the relationship between intraoperative sarcomere length and the extent of contracture was measured in 23 children (average age, 14.3 +/- 2.9 years) undergoing tendon transfers involving the flexor carpi ulnaris (FCU) or extensor carp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 38 publications
2
45
2
1
Order By: Relevance
“…A possible explanation for the shorter fascicles may be a loss of serial sarcomeres. Several studies have shown that sarcomeres in spastic muscles are longer than in normal muscles when measured at defined joint angles (Lieber and Friden, 2002;Pontén et al, 2007). Since the fascicles are shorter, and the sarcomeres are longer, the number of serial sarcomeres in spastic muscles must be smaller.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A possible explanation for the shorter fascicles may be a loss of serial sarcomeres. Several studies have shown that sarcomeres in spastic muscles are longer than in normal muscles when measured at defined joint angles (Lieber and Friden, 2002;Pontén et al, 2007). Since the fascicles are shorter, and the sarcomeres are longer, the number of serial sarcomeres in spastic muscles must be smaller.…”
Section: Discussionmentioning
confidence: 98%
“…The passive muscle stiffness and the joint contractures have been proven harder to explain. Sarcomere lengths have been studied, and have been reported to be longer in the flexor carpi ulnaris muscle in spastic CP patients compared to control (Lieber and Friden, 2002;Pontén et al, 2007), suggesting that sarcomeres were operating primarily on the descending limb of the force-length relationship (Gordon et al, 1966) for children with CP.…”
Section: Introductionmentioning
confidence: 98%
“…The inherent larger physiologic cross-sectional area (and thus strength) of the wrist flexors compared to wrist extensors [15] will then drive the wrist into flexion. Third, there is a likely loss of sarcomeres and the muscle tendon unit is stiffer than normal [21].…”
Section: Introductionmentioning
confidence: 99%
“…midfoot and hindfoot, increasing stance phase ankle dorsiflexion, and increasing knee and hip flexion as children grow [4,[11][12][13]. The evolution of flexed-knee gait often includes knee pain (resulting from apophysitis of the distal pole of the patella and tibial tubercle), increasing torsional malalignment of the lower extremity, increasing foot pain, posterior knee capsule contracture, and progressive loss of gait function during adolescent growth [1,3,4,14].…”
mentioning
confidence: 99%
“…The evolution of flexed-knee gait often includes knee pain (resulting from apophysitis of the distal pole of the patella and tibial tubercle), increasing torsional malalignment of the lower extremity, increasing foot pain, posterior knee capsule contracture, and progressive loss of gait function during adolescent growth [1,3,4,14]. This evolution is a probable cause of loss of ambulation in severe cases [14].…”
mentioning
confidence: 99%